Brometalia erecti Br.-Bl. 1936 grasslands from Antiapennine calcareous massifs of central-southern Tuscany (central Italy) - Angiolini, Claudia; Riccucci, Costanza; Dominicis, Vincenzo de (Lazaroa, 2003)
Floristic characteristics, syntaxonomy and synecology of grasslands of the order Brometalia erecti on calcareous massifs of central-southern Tuscany are reported. Multivariate analysis was used to compare 64 phytosociological relevés made in the years 1997, 2000 and 2001. These pastures occur in areas of the temperate oceanic region, with upper hill to montane thermotype and lower humid to lower hyperhumid ombrotype, in serial contact with woods of Ostrya carpinifolia Scop. and with beech woods on summits. The plant communities surveyed were clasified in the following assciations: i) Cerastio etrusci-Brometum erecti ass. nova (Phleo-Bromion Biondi & Blasi ex Biondi & al. 1995), identified for serie grasslands on moderate to steep slopes with basic lithosoils in the hill and lower montane belts; it has two variants related to soil chemical and physical characters: comparison with similar vegetation of other Apeninne areas confirms the western connotation and autonomous nature of these communities; ii) Trifolio incarnate-Brometum erecti Oberdorfer & Hofman 1967 (Bromion W. Koch 1926), known from the Ligurian Apennine downwards; in the area studied it shows a new “Antiapenninic” subassociation named phleetosum ambigui that includes: a mesophilous variant with Arrhenatherum elatius, related to flat or north-exposed stations in the mountain belt; linked to mature soils with high moisture all year, rich in transgressive species of the class Molinio-Arrhenatheretea Tüxen 1937: a subnitrophilous variant with Carlina corymbosa, related to grazing and exclusive to soils wiht high clay component: a transition variant towards xerophilous grasslands. The study confirms the presence of the alliance Phleo-Bromion in Tuscany as an isolated appendage with northern outposts of xerocalcicolous communities widespread in the central-southern Apennine: a similarity with vegetation of northern Tyrrhenian sectors was also observed.